PERBANDINGAN KUNJUNGAN PASIEN PER KASUS DI PELAYANAN KESEHATAN GIGI LANJUTAN PADA RUMAH SAKIT DI KOTA PADANG DITINJAU DARI PEMANFAATAN SISTEM JAMINAN KESEHATAN NASIONAL (JKN) - Diva Indah Pratiwi; Rima Semiarty; Aria Fransiska (Andalas Dental Journal, 2015)
Implementation of the National Health Insurance (JKN) in Padang’s Hospital has started since 1 January 2014. In practice JKN implement tiered referral system of first-level health facilities to advanced-level health facilities to meet the needs of the patient. This study aimed to compare the level of patient visits before and after JKN and to determine the causes of the referral hospital, especially in Yos Sudarso Padang Hospital and dr. Rasidin Regional Public Hospital Padang.This research is a qualitative descriptive study. Data collection was done by taking the primary data from hospitals and depth interviews with dentists and patients at first-level health facilities and advanced. Data processing is done by reducing the data, presentation of data, drawing conclusions, and analysis of data.The results showed that the level of patient visits Yos Sudarso Padang Hospital increased while at the dr. Rasidin Regional Public Hospital Padang decreased. Level visits patients in Yos Sudarso Padang Hospital increased due to the lack of expertise and infrastructure at the first level of health care. While at dr. Rasidin Regional Public Hospital Padang level of patient visits decreased due to distant location of the hospital and the lack of transportation to the hospital.JKN implementation has been running quite optimal, but still there are patients who complain of difficulty in obtaining health services, especially in the first-level health facilities.